Socioeconomic and dental profile of pre-kidney transplant patients followed up at a reference medical center in the State of Ceará (Research, Society and Development, 2025)
This study aims to assess the socioeconomic and dental profile of pre-kidney transplant patients. A survey of the socioeconomic and dental profile of Chronic Kidney Disease (CKD) patients at the Hospital Geral de Fortaleza (HGF) was carried out in August/2023, in order to characterize and collect data to assist in planning and optimizing care. Patients over 18 years of age were included, and those with previous dental treatment at HGF, unstable carriers of Human Immunodeficiency Virus (HIV), hepatitis B and C, pregnant women, and those who did not sign the Free and Informed Consent Form were excluded. Anamnesis, clinical and hematological examinations were performed on 30 patients, complemented by the BOAS-m Scale (Modified Beck Oral Assessment Scale) and the DMFT index (Missing, Filled and Decayed Teeth), using a significance level of 95%. It was found that 60% had a disease progression of 1 to 4 years, red blood cells (43.3%) and hemoglobin (46.7%) were reduced, urea (96.7%) and creatinine (100%) were elevated. Dental rehabilitation was required in 83.3%, 53.4% having reported complaints of pain, aesthetics, chewing, bleeding and xerostomia, as well as 66.7% having not been to the dentist for more than 1 year and 26.7% feeling resistance to dental care outside the Hospital. The DMFT was characterized as very high (17.53 ± 8.09) and the BOAS-m scale (8.60 ± 2.28), mild. Correlating the variables with the BOAS-m scale, no statistically relevant results were found that associated the oral conditions with the anamnesis performed (p > 0.05). CKD patients presented multiple needs when arriving at the Dentistry service, reiterating the importance of the presence of a dentist during the pre- and post-operative period.